Women in PR history
1 online resource (x, 120 pages)
Keywords: "This book explores the field in a way that will offer insight of the significance that women had in the evolution of PR, with diverse chapters that provide rich perspectives on women's contributions to PR throughout the years and across the globe.. The book opens with an overview of women in public relations. Later chapters focus on the case of Turkey, which seems to have a rich history of women in public relations, then focus on specific cases from Oceania (Australia), Europe (Spain), Asia (Malaysia and Thailand) and America (US). The final chapter deals with the case of Inez Kaiser, who was the first African-American women to open a U.S. public relations agency"--